Social stratification in a global successful activity: the case of wine industry in Mendoza (1995-2011) - Heredia, Mariana; Poblete, Lorena (Centro de Historia Argentina y Americana, 2013)
In order to contribute to the knowledge of social inequalities in contemporary Argentina, this article examines how the restructuring of the wine from Mendoza (which begun in the late eighties and consolidated in the year two thousand) resulted in the restructuring of different socio-professional categories and their ties. The speed and depth of these transformations, in a relatively limited space and in an economic activity that is judged as a successful case of integration into the international market make Mendoza wine’s industry a privileged case to discuss social impact of agribusiness’ transnationalization